Examining graphemic and lexical anglicisms in Twi for academic purposes in textbooks written in Twi - Akoto, Osei Yaw; Marfo, Charles Ofosu; Ansah, Juliet Oppong-Asare; Fordjour, Emmanuel Antwi; Forson, Isaac Adjei (Linguistik Online, 2022)
This paper examines graphemic and lexical borrowings in Twi for Academic Purposes (TAP). Textbooks written in Asante Twi by some renowned scholars in the language constituted the dataset for this study. The textbooks were read and all instances of anglicisms or English features borrowed into Twi were collected. The borrowed-features were identified by drawing on our native speaker and scholarly competencies. The dataset was analyzed by drawing on Clyne’s (1977) Borrowing Typology and Haugen’s (1950) Borrowability Scale. Three key findings emerged from the analysis. First, the study yielded that in TAP two letters (<v>, and <j>) are borrowed towards empowering Asante Twi to enable it to account for words that contain these letters. Second, at the lexical level, it was found that the borrowed words were either integrated or adapted into Asante Twi linguistic environment. The final point was that all the lexical items realized were nominals affirming the primacy of noun on borrowability scales. The findings have implications for developing Ghanaian languages for academic purposes.